Study of hot processing map of AISI 1035 steel under high temperature - G. C. Yu; G. Song; C. Han; Y. Z. Zhong; H. C. Ji; J. Yuan (Metalurgija, 2023)
In this study, AISI 1035 steel was selected as the research object, and a single-pass thermal compression simulation experiment was carried out. Based on the true stress-strain curve obtained from the experiment, the dynamic DMM thermal processing map theory was used to draw the material under different thermal deformation conditions. and the rheological instability map based on the Prasad instability criterion, and the thermal processing map is used to predict the suitable processing interval and rheological instability interval for the thermal deformation process of the material under different process conditions. So as to provide theoretical support for the optimization of the material processing technology.